2012
DOI: 10.1094/pdis-11-11-0979
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Spot Disease Caused by Exserohilum rostratum on Pineapple in Hainan Province, China

Abstract: Planf Dis. 96:458, 2012; published online as http://dx.doi.org/I0.1094/PDlS-07-ll-0620. Accepted for publicafion 10 December 2011.In June 2011, sympfoms of posfbarvest rot were observed on approximafely 3% of all cherries collected from commercial orchards of culfivars Lapen and Ferrovia in fbe prefectures of Imathia and Pella (northern Greece). Fruif were harvesfed in a timely manner fo avoid overripeness. No wounds or ofher predisposing injuries were observed on the infected fruits. Lesions enlarged rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Exserohilum species are common molds found in soil and on plants, especially grasses, and they thrive in humid climates. Some species can cause severe plant disease epidemics [31] , [42] . Exserohilum rostratum has been recorded as a minor pathogen of humans, mainly in immunocompromised patients [29] , but proved to be deadly when injected in the epidural space around the spinal column as a contaminant in a corticosteroid fluid [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exserohilum species are common molds found in soil and on plants, especially grasses, and they thrive in humid climates. Some species can cause severe plant disease epidemics [31] , [42] . Exserohilum rostratum has been recorded as a minor pathogen of humans, mainly in immunocompromised patients [29] , but proved to be deadly when injected in the epidural space around the spinal column as a contaminant in a corticosteroid fluid [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Many Exserohilum species are plant pathogens that cause distinct leaf spots and blights. E. rostratum is a plant pathogen that affects a wide range of species, particularly grasses, Poaceae [30] , but also other monocotyledonous plant families [31] . However, under certain circumstances E. rostratum can survive and thrive in human and animal hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf spot diseases of pineapple are always considered less important unless the diseases severely attack the whole plant. Many leaf spot diseases have been reported on pineapple plants such as leaf spot caused by Exserohilum rostratum (Luo et al, 2012) and leaf spot caused by Curvularia clavata (Zhong et al, 2016) found in China. Leaf spot disease can also be caused by Chalara parodoxa as reported by Joy and Sindhu, (2012) in India.…”
Section: Causal Pathogenmentioning
confidence: 99%
“…1b). The fungus was reisolated from leaf Exserohilum rostratum has been reported previously on many monocotyledonous plants (Sivanesan 1987;Leonard et al 1988;Cardona and González 2007;Luo et al 2012), S. officinarum (Zummo 1986) and turfgrass species in Iran (Mirabolfathi and Ershad 2006). To our knowledge, this is the first report of leaf spot caused by E. rostratum on S. officinarum in Iran.…”
mentioning
confidence: 94%
“…Pathogenicity tests were conducted on 2-month-old sugarcane plants by spraying a conidial suspension of the fungus (10 5 conidia/ml of water) (Luo et al 2012). The pathogenicity tests were conducted using three replicates for each isolate (Ex 1, Ex 2 and Ex 3), two plants for each replicate and the inoculated plants were held in a greenhouse under ambient conditions (20-25°C, 75-85 % RH).…”
mentioning
confidence: 99%